Transformer rail-tapped buck-boost converter design-based feedback controller for battery charging systems - Dagal, Idriss; Akin, Burak (WILEY, 2023)
In this article, a transformer rail-tapped buck-boost converter (TRT-BBC) with minor loss of power transfer from a photovoltaic solar panel to a lead-acid battery for battery charging systems is designed. The TRT-BBC has been utilized to inter-match the PV direct power to the battery. The 24-V lead acid battery bank with a storage energy of approximately 168 Wh is designed. The photovoltaic solar panel of 200 W maximum power is used for the whole system operation. The proposed TRT-BBC topology solves the conventional buck-boost converter inverted output problem with apex conversion efficiencies of 93.25% and 91.97% for continuous current mode (CCM) and discontinuous current mode (DCM) respectively at standard test conditions (STC) and full load conditions. The whole system can operate either in DCM or CCM according to the needs at a switching frequency of 100 kHz and the maximum power point tracking (MPPT) with proportional integration (PI) based constant voltage-constant current (CV-CC) feedback control loop used to monitor the switching duty cycle of the TRT-BBC.
Keywords: buck-boost converter; conversion efficiency; photovoltaic; rail-tapped transformer; tracking efficiency; Energy & Fuels